Detecting Change in Conjunctival Hyperemia Using a Pixel Densitometry Index. (17th February 2019) - Romano, Vito; Steger, Bernhard; Brunner, Matthias; Kaye, Abigail; Zheng, Yalin; Willoughby, Colin E.; Kaye, Stephen B.
ABSTRACT: Purpose : To investigate a pixel densitometry index (PDI) for measuring ocular surface inflammation (OSI). Methods : Efron's grading was performed by two independent observers. Color photographs and indocyanine green angiography were undertaken before and after instillation of phenylephrine (PE) hydrochloride 2.5%. Results : A total of 15 patients with and 10 without OSI were included. PDI before and after PE was 73.29 ± 30.71 and 50.87 ± 17.46 ( p = 0.036) in patients with inflammation and 52.86 ± 16.90 and 39.63 ± 12.04 ( p = 0.0024) in those without OSI. The reduction in Efron grades following PE was 25% (mean 0.46 ± 0.50, median 0.50; p < 0.01). The coefficient of variation pre- and post-PE was lower using the PDI (42% and 50%) than with the Efron grades (59% and 72%). Conclusion : The PDI allows the objective detection of change in conjunctival hyperemia with potential direct applicability to noninvasive angiography such as optical coherence tomography-based angiography.